Pengaruh Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Peternakan Unggas pada Peserta Didik Kelas XI SMK Negeri 1 Talibura - Siti Mudiah; Nur Chotimah; Amir Djonu (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
This study aims to find the effect of entrepreneurial knowledge on interest in poultry farming entrepreneurship in class XI students of SMK Negeri 1 Talibura. This research was conducted at SMK Negeri 1 Talibura. The population in this study were class XI students of poultry farming. The sample in this study amounted to 67 people. The sampling technique used is random sampling technique with the term random sampling. This research uses descriptive method and quantitative approach. All statements are valid, reliable, normal, linear. Based on the results of simple linear regression calculations, it is obtained that interest in entrepreneurship = 72.061 + 0.439 (knowledge of entrepreneurship). Testing the hypothesis from the calculation of the t test results obtained tcount > ttable 1.689> 1.667), which means that ho is rejected and h1 is accepted. The results show that the coefficient of determination (R Square) of the independent variable on the dependent variable is R2 = 0.487 or 48.7%. So, the results of this study concluded that there was a positive and significant influence on entrepreneurial knowledge on the interest in entrepreneurship in poultry farming in Class XI students of SMK Negeri 1 Talibura.